Paraurethral Leiomyoma in a Postmenopausal Woman: First European Case - Susy Shim; Camilla Skovvang Borg; Huda Galib Majeed; Peter Humaidan (Case Reports in Obstetrics and Gynecology)
Leiomyomas are benign tumors extending from smooth muscle cells and only few cases of paraurethral leiomyomas have been described in the literature. They are often seen in the reproductive age and around 50% of the cases are asymptomatic. We describe a 59-year-old woman with a solid mobile tumor below the symphysis revealed at a gynecological examination. Transvaginal ultrasound and MRI confirmed the tumor and excision of the paraurethral tumor was carried out. The histological examination showed a benign paraurethral leiomyoma. The postoperative period was characterized by urethral pain as well as vaginal leakage of urine.